Analisis Pengaruh Luas Lahan dan Sumber Penghasilan terhadap Pendapatan Rumah Tangga Usaha Pertanian - N, Zulkifli; Karimi, Syafruddin; Taifur, Werry Darta; Ridwan, Endrizal (SAFE-Network, 2023)
This study examines the effect of land area and income sources of agricultural households on their income in the context of reducing poverty in the agricultural sector. This study uses a quantitative approach and multiple regression methods as an analytical tool with data from the Agricultural Business Household Income Survey which is part of the 2013 Agricultural Census of West Sumatra Province. The data used in this study is cross-sectional data with total agricultural household income as the dependent variable and the amount of land owned by agricultural households, the area of ​​land controlled and cultivated by agricultural households, the percentage of agricultural household income from agricultural sector businesses, the percentage of agricultural household income from non-agricultural businesses, the percentage of other agricultural household income , the percentage of agricultural household income from wages in the agricultural sector, and the percentage of agricultural household income non-agricultural wage income. The results showed that the variable area of ​​land owned and the area of ​​land controlled and cultivated by agricultural households had a positive effect on their total income. Other variables that have a positive effect on total agricultural household income are the percentage of income from non-agricultural businesses and the percentage of non-agricultural wage income. On the other hand, the percentage of agricultural household income from agricultural sector businesses and the percentage of agricultural household income from wages in the agricultural sector have a negative effect on their total income. The results of this study suggest the need for redistribution of land to land-poor agricultural households and encourage them to diversify their business outside the agricultural sector but still based on agricultural products.